Dosis de ácido indolbutírico y tipos de sustratos en el enraizamiento de estaquillas de copaifera paupera (herzog) dwyer “copaiba” en bandejas porta tubetas Puerto Almendra, Loreto- Perú 2022 - Pizarro Góngora, Francisco Martín Tomás (2024)
The study, conducted at the Center for Provenance of Agricultural and Forest Species in the Peruvian Amazon, aimed to determine the effect of indolebutyric acid (IBA) doses and substrates types on the rooting of Copaifera paupera cuttings in plug trays. The research employed a 4x2 factorial experimental design with a quantitative approach and explanatory level. Results indicated that the substrate factor was more influential than IBA doses in callus formation (p=0.0166) and cutting survival (p=0.0204). The most effective treatment was T5 (agricultural perlite + 0 ppm IBA), achieving 66.67% callus formation and 70.83% survival. Fort he rooting variable, analysis of variance was not performed due to the low number of rooted cuttings (3). However, treatment T4 (calcined rice husk + 6000 ppm IBA) showed the greatest root length (85 mm).